2022
DOI: 10.3390/ijms23126382
|View full text |Cite
|
Sign up to set email alerts
|

Canine Circovirus Suppresses the Type I Interferon Response and Protein Expression but Promotes CPV-2 Replication

Abstract: Canine circovirus (CanineCV) is an emerging virus in canines. Since the first strain of CanineCV was reported in 2012, CanineCV infection has shown a trend toward becoming a global epidemic. CanineCV infection often occurs with coinfection with other pathogens that may aggravate the symptoms of disease in affected dogs. Currently, CanineCV has not been successfully isolated by laboratories, resulting in a lack of clarity regarding its physicochemical properties, replication process, and pathogenic characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…There may be several reasons for vaccine failure. Among them, interference of maternal antibodies may be an important factor [ 38 ], or coinfection with other viruses may lead to immunosuppression in dogs [ 39 , 40 , 41 ]; the greatest probability is a change in the antigenicity of the virus. At present, the vaccine commonly used in China is still original CPV-2 or CPV-2b [ 16 ], and vaccination failure is related to a large extent to the poor protection of CPV-2c [ 15 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…There may be several reasons for vaccine failure. Among them, interference of maternal antibodies may be an important factor [ 38 ], or coinfection with other viruses may lead to immunosuppression in dogs [ 39 , 40 , 41 ]; the greatest probability is a change in the antigenicity of the virus. At present, the vaccine commonly used in China is still original CPV-2 or CPV-2b [ 16 ], and vaccination failure is related to a large extent to the poor protection of CPV-2c [ 15 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The finding of CanineCV viral genomes by ISH and viral protein by IHC indicates active viral infection, providing strong support for the hypothesis of CanineCV-associated respiratory disease. Only one study demonstrated that CanineCV suppressed the antiviral response of infected cells by inhibiting type 1 interferon, which results in the enhancement of canine parvovirus replication ( 12 ). In the PCV2 study, infection of PCV2 in pulmonary alveolar macrophages disrupted the function of these cells, consequently promoting respiratory bacterial infection ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…The exact role of the virus in these cells remains uncertain. Only one published article has shown the suppression of the interferon response in the cells infected with CanineCV ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Competition may arise between viruses via processes such as interferon-mediated immunity or resource competition [ 165 , 166 ]. Alternatively, facilitation can occur through immune suppression, or upregulated viral replication [ 167 , 168 ]. In general, however, we found scant evidence of pairwise associations at the level of viral families, with the viral composition of co-infections in our database being instead consistent with testing effort.…”
Section: Discussionmentioning
confidence: 99%